(3GdJRhjQ GdeYdheGJj ddYdGeI GdJLGQjI (B:s (3OQGSI JMdjdI JCUjdjI eRhOI heOYeI HGdGLJgGOGJ GdbVGFjI (B= Information fraud of the trademark : analytical and original study provided and supported by judicial opinions /s - (3GdcShGfj, YGeQ eMehOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2014)
(3jJfGhd cJGH (B((3GdJRhjQ GdeYdheGJj ddYdGeI GdJLGQjI (B: (3OQGSI JMdjdI JCUjdjI eRhOI heOYeI HGdGLJgGOGJ GdbVGFjI(B) (3hGdPj bGe HJCdjag (B((3YGeQ eMehO GdcShGfj(B) (3aj MhGdj (B(240 (3UaMI(B) (3ef GdbWY GdeJhSW ehVhY (B((3GdYdGeGJ GdJLGQjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdHGH GdChd (B: (3fXQI YGeI Ydi GdYdGeI GdJLGQjI, GdaUd GdChd (B: (3GdfTCI GdJGQjNjI ddYdGeI GdJLGQjI, GdaUd GdKGfj (B: (3CgejI GdYdGeI GdJLGQjI, GdaUd GdKGdK (B: (3hXjaI GdYdGeI GdJLGQjI, GdaUd GdQGHY (B: (3TQhW GdYdGeI GdJLGQjI, GdaUd GdNGeS (B: (3JYQja GdYdGeI GdJLGQjI, GdaUd GdSGOS (B: (3GdYdGeI GdJLGQjI hHGbj eaQOGJ GdedcjI GdacQjI, GdHGH GdKGfj (B: (3LQjeI JRhjQ GdYGeI GdJLGQjI HUhQJgG GdeYdheGJjI, GdaUd GdJegjOj (B: (3GdLQGFe GdeYdheGJjI, GdaUd GdChd (B: (3XGgQI JRhjQ GdYdGeI GdJLGQjI, GdaUd GdKGfj (B: (3GdQcf GdeGOj ddJRhjQ heOi GfWHGbg Ydi GdJRhjQ GdeYdheGJj, GdaUd GdKGdK (B: (3GdQcf GdeYfhj dLQjeI JRhjQ GdYdGeI GdJLGQjI heOi GfWHGbg Ydi GdJRhjQ GdeYdheGJj, GdaUd GdQGHY (B: (3YbhHI JRhjQ GdYdGeI GdJLGQjI, GdaUd GdNGeS (B: (3LQjeI GSJYeGd GdYdGeI GdJLGQjI GdeRhQI eYdheGJjG(B.s
(3HHdjhLQGajI (B: (3UaMI (B237-240.s
Keywords: (3GdYdGeGJ GdJLGQjIs -- (3bhGfjf hJTQjYGJs; (3GdJRhjQs -- (3bhGfjf hJTQjYGJs -- (3eYGdLI HjGfGJs; (3GdLQGFe GdMGShHjI s -- (3bhGfjf hJTQjYGJs